Feasibility Of Providing Educational Counseling In Needle-Syringe Exchange Programs In Penang, Malaysia - Shamandi, Zohreh (2012)
Providing education on health risks and treatment opportunities may enhance harm reduction effectiveness of Needle-Syringe Exchange Program (NSEP) and lead to more engagement for drug addiction treatment. To evaluate the feasibility of providing an extended and structured Educational Counseling (EC) program to active drug injectors in the NSEPs , and to assess their EC participation, drug treatment enrollment and HIV risk behaviors. In a purposive-opportunistic sampling, a total of 124 active heroin injectors participating in NSEPs were screened, 98 met the entry criteria and expressed interest to participate in weekly group Educational Counseling for 10 sessions, followed by 3 months of follow-up in monthly intervals.